2008
DOI: 10.1097/olq.0b013e31815abab5
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Sexual and Drug Using Behaviors Among Male Injection Drug Users Who Have Sex With Men in 2 Mexico-US Border Cities

Abstract: Objectives-The population of Latino men who have sex with men (MSM) and who are also injection drug users (IDUs) is understudied. We explored risk behaviors of MSM/IDUs compared with other male IDUs in 2 Mexican border cities.Study Design-In 2005, IDUs who had injected within the previous 30 days were recruited using respondent-driven sampling (RDS) in Tijuana and Ciudad Juárez. They underwent antibody testing for HIV, HCV, and syphilis and interviewer-administered surveys. Men were categorized as MSM if they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 46 publications
5
38
0
1
Order By: Relevance
“…Some RDS studies have found fewer sexual partners than in this study 24,28,39,40 , but our findings are close to other results of RDS studies with MSM 6,25,27,30 . Still, such differences may be due to the lack of a standardized period for which the number of partners was computed, varying widely in the literature, or to characteristics like the size of MSM social networks, age, schooling, and social class, factors that may be associated with the number of sexual partners in this sample.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Some RDS studies have found fewer sexual partners than in this study 24,28,39,40 , but our findings are close to other results of RDS studies with MSM 6,25,27,30 . Still, such differences may be due to the lack of a standardized period for which the number of partners was computed, varying widely in the literature, or to characteristics like the size of MSM social networks, age, schooling, and social class, factors that may be associated with the number of sexual partners in this sample.…”
Section: Discussionsupporting
confidence: 79%
“…As for syphilis, the prevalence found in Salvador is close to that reported in the international literature 2,5,7,8,9 , including RDS studies with MSM 6,30 , and shows the high prevalence of syphilis among MSM interviewed.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…For NHBS-IDU-2, a sample of IDU was recruited between August and November 2009 via respondent-driven sampling (RDS), a chain-referral method which accesses hard to reach populations and provides estimates generalizable to the population of networks from which they are drawn; this method has been used in populations of IDU by other authors. [25][26][27][28][29][30][31][32][33][34][35][36] Non-randomly identified "seeds" are given coupons to recruit three people from their social and/or sexual networks to join the study, and each subsequent eligible person completing the interview is provided with up to three coupons with which to recruit their network members. Eligible individuals lived in the metropolitan DC area, were 18 years old and older, and injected drugs in the past 12 months based on verification of injection sites or successful completion of a knowledge screener specific to IDU.…”
Section: Methodsmentioning
confidence: 99%